ENTREPRENEURSHIP CHARACTER EDUCATION THROUGH THE MARKET DAY PROGRAM - Mei Hastuti; Maslamah Maslamah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
Soft skill (everyday life character) and academic capability (hard skill) must be integrated in the implementation of education to create excellent and civilized human resources. A country can be said to be prosperous if many citizens become entrepreneurs, and the entrepreneurial character will be excellent when it is formed in early age. The Market Day program is a student entrepreneurship development facility and aims to train students' entrepreneurial character. This research is aimed to explain how entrepreneurship characters formed through market day program at SDIT Insan Kamil Karanganyar. This study used a qualitative descriptive method. The data collected through observation and interview, then data analyzed using Miles & Huberman model. The results of showed the process of achieving entrepreneurial character through a series of Market Day referring to the values ??of 10 muhasofat/human qualities. The activities consisted of planning/planning, implementation (market simulation), and evaluation. Several types of entrepreneurial values ??applied in the program are: 1) honesty, 2) discipline, 3) creativity, 4) independence, 5) hard work, and 6) friendship/communication with others.